2013
DOI: 10.1248/bpb.b12-00968
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone Suppresses the Proliferation of RAW264.7 Macrophage Cells via Glucocorticoid, But Not Mineralocorticoid, Receptor

Abstract: Macrophages are white blood cells within tissues that are produced by monocytes and help to protect against infection by bacteria through phagocytosis. Several studies have shown a correlation between the state of depression and abnormalities in the immune response. Corticosterone (CORT), which is often referred to as the stress hormone, is a well-known regulator of peripheral immune responses and also shows anti-inflammatory properties in the body. However, it is still unclear how CORT regulates macrophage fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…To explore whether XYS could suppress the lipid accumulation induced by CORT, we generated an ox-LDL and CORTinduced stress model in rat PMs following the treatment of XYS-containing serum. Our results showed that CORTinduced stress inhibited proliferation and increased lipid accumulation in PMs, which was similar to the results of previous studies (24,25). We also found that serum including XYS could dose-dependently increase proliferation, decrease lipid accumulation, and elevate TC level in CORT-induced PMs.…”
Section: Discussionsupporting
confidence: 91%
“…To explore whether XYS could suppress the lipid accumulation induced by CORT, we generated an ox-LDL and CORTinduced stress model in rat PMs following the treatment of XYS-containing serum. Our results showed that CORTinduced stress inhibited proliferation and increased lipid accumulation in PMs, which was similar to the results of previous studies (24,25). We also found that serum including XYS could dose-dependently increase proliferation, decrease lipid accumulation, and elevate TC level in CORT-induced PMs.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement, several studies have reported that glucocorticoids decreases proliferation of lymphocytes, 6 broblasts and macrophages. 29,30 In addition, no differences were observed between coaxial PCL/PEO hollow-Dex and Dex added directly in the culture media, suggesting that even though a 38% of the theoretical total amount of Dex loaded was still not released at the end of the in vitro study (day 3), a signicant reduction in cell growth of inammated cells was observed. Further, the results from LDH assay (Fig.…”
Section: Cell Proliferationmentioning
confidence: 98%
“…With regards to the effect on non-specific cellular immunity, previous studies have demonstrated that chronic stress can weaken natural killer (NK) cell function and inhibit their activity, promoting tumor progression (65). Stress can also stimulate macrophages or monocytes to secrete interleukin (IL)-1, IL-6 and tumor necrosis factor (TNF)-α, but reduce the secretion of IL-2, IFN-γ and major histocompatibility complex (MHC), which may aid tumor cells to evade immune surveillance (66,67). Tumor associated-macrophages (TAMs) are one of the components of the tumor microenvironment in which stress can increase tumor infiltration by macrophages, and macrophage infiltration can mediate stress-enhanced metastasis in primary breast cancer (68).…”
Section: Mechanisms Underlying the Effects Of Stress On Tumorigenesismentioning
confidence: 99%